2016
DOI: 10.5194/acp-16-14527-2016
|View full text |Cite
|
Sign up to set email alerts
|

Detection of atmospheric gaseous amines and amides by a high-resolution time-of-flight chemical ionization mass spectrometer with protonated ethanol reagent ions

Abstract: Abstract. Amines and amides are important atmospheric organic-nitrogen compounds but high time resolution, highly sensitive, and simultaneous ambient measurements of these species are rather sparse. Here, we present the development of a high-resolution time-of-flight chemical ionization mass spectrometer (HR-ToF-CIMS) method, utilizing protonated ethanol as reagent ions to simultaneously detect atmospheric gaseous amines (C1 to C6) and amides (C1 to C6). This method possesses sensitivities of 5.6–19.4 Hz pptv−… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
121
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 62 publications
13
121
0
1
Order By: Relevance
“…1 × 10 6 to 3 × 10 7 cm −3 , which fall into the range for most observations of atmospheric boundary layer NPF events (e.g., Kulmala et al, 2013). The DMA mixing ratio for most of the data shown in this study is ∼ 40 pptv (1 × 10 9 cm −3 ), which is within the rather wide range of observations (0.1 to 157 pptv, i.e., 2.5 × 10 6 to 4 × 10 9 cm −3 ) for C2-amines to which DMA belongs (Yao et al, 2016).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…1 × 10 6 to 3 × 10 7 cm −3 , which fall into the range for most observations of atmospheric boundary layer NPF events (e.g., Kulmala et al, 2013). The DMA mixing ratio for most of the data shown in this study is ∼ 40 pptv (1 × 10 9 cm −3 ), which is within the rather wide range of observations (0.1 to 157 pptv, i.e., 2.5 × 10 6 to 4 × 10 9 cm −3 ) for C2-amines to which DMA belongs (Yao et al, 2016).…”
mentioning
confidence: 60%
“…Despite the strong evidence that sulfuric acid-amine nucleation is very efficient, it has rarely been observed in the atmosphere. Only one study has so far reported sulfuric acid-amine nucleation (Zhao et al, 2011) despite amine mixing ratios of up to tens of parts per trillion volume at some sites (Yu and Lee, 2012;You et al, 2014;Freshour et al, 2014;Yao et al, 2016). A global modeling study of sulfuric acid-amine nucleation has been carried out so far (Bergman et al, 2015), applying a nucleation parametrization based on the measurements of Almeida et al (2013) and Glasoe et al (2015).…”
mentioning
confidence: 99%
“…Hanson et al () and Zheng et al () have used protonated water ions as reagent to measure various amines and ammonia. H. Yu and Lee () applied protonated ethanol and acetone ions as reagent to detect amines and ammonia together, and this ion‐molecule reaction scheme later was applied for amine measurements also by other groups (Yao et al, ; Yao et al, ). Either quadrupole mass spectrometry or high‐resolution time of flight mass spectrometer (HR‐TOF‐MS) has been used as detector.…”
Section: Development Of New Instrumentsmentioning
confidence: 99%
“…Such a correlation was also reported by other researchers Yu et al, 2005), suggesting the co-occurrence and internally mixing state of both compounds in the atmosphere. In addition, the previous field measurements also revealed that WSOM in China is not only enriched in carboxylic acids (including oxalic acid) but also in other organic species, including carbonyls, amines, and water-soluble nitrogen-containing organic compounds (G. Wang et al, 2010;Wang et al, 2013;Zheng et al, 2015;Yao et al, 2016;F. Liu et al, 2017).…”
Section: Field Measurements Of Wsom In Chinamentioning
confidence: 99%
“…Also, organic acids engage in particle-phase reactions with the basic species (i.e., NH 3 and amines), significantly enhancing the particle hygroscopicity and reducing the acidity (GomezHernandez et al, 2016). In addition, because of their strong basicity and high abundance, amines likely play a key role in reducing the particle acidity in China (L. Wang et al, 2010a, b;Qiu et al, 2011;Qiu and Zhang, 2012;Dong et al, 2013;Zheng et al, 2015;Yao et al, 2016;F. Liu et al, 2017).…”
Section: Field Measurements Of Wsom In Chinamentioning
confidence: 99%